Amigos, amigos, negócios a parte! o jogo de interesses entre Brasil e Estados Unidos no período de 1942 a 1951 - Tobias, Fabio Lucio Mello (2018)
A part of the most considered conjectures about the relations between Brazil and the United States insists that Brazil, at some key moments in its history, was subservient to Washington's interests, automatically aligning itself with the interests of the Americans . With the beginning of World War II in 1939, the configuration of power relations between countries began to change, affecting in a political or economic way almost the entire planet. In the case of Brazil, starting in 1942 the country began to participate in a game of interests with the United States that, among other things, wished to have access to the air bases of the Northeast. The Vargas government (1930-1945) and following the Dutra government (1946-1951), saw in this conjuncture an opportunity of negotiation, took advantage of the situation and negotiated with the Americans, trying to gain some advantages for the country. In this game, World War II and the Cold War served as a field for agencies such as the OSS, OCIAA and CIA, in the service of the United States and guaranteed the country some advantages. On the other hand, we did not have that many players, but we never stopped playing. We have even taken up space in newly created international forums such as the UN, OAS and ECLAC, among others. Not always winning, not always losing, but learning to play. Analyzing the Brazilian performance in these organizations, we intend to demonstrate that even in the face of various difficulties and in a less favored situation, the Brazilian government tried, with the resources it had at the time, to be protagonists of its own history